Cranford [videorecording (DVD)] - Birtwistle, Sue; Conklin, Susie (Masterpiece theatre series., 2008)
Cranford, in 1842, is a market town in northwest England. It is a place governed by etiquette, custom and above all, an intricate network of ladies. It seems that life has always been conducted according to their social rules. For spinsters Deborah Jenkyns, the arbiter of correctness, and Matty, her demurring sister, the town is a hub of intrigue. Handsome new doctor Frank Harrison has arrived from London; a retired Captain and his daughters move in across the street and preparations for Lady Ludlow's garden party are underway. The town has some secrets which are about to be revealed. But news comes that shakes the town: a railway line from Manchester is coming to Cranford.